2021
DOI: 10.3390/met11050778
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Additive Manufactured Stainless Steel Tool Electrode on Machinability of Beta Titanium Alloy

Abstract: Additive manufacturing technology provides a gateway to completely new horizons for producing a wide range of components, such as manufacturing, medicine, aerospace, automotive, and space explorations, especially in non-conventional manufacturing processes. The present study analyzes the influence of the additive manufactured tool in electrochemical micromachining (ECMM) on machining beta titanium alloy. The influence of different machining parameters, such as applied voltage, electrolytic concentration, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…A very impressive hardness value was reached (after ECAP route Bc for four passes) of 110 HV, along with an ultimate compressive strength of 185 MPa. The hardness observed in the ECAP-compacted alloy was mainly attributed to the dispersion hardening of Y 2 O 3 particles [7].…”
Section: Contributionsmentioning
confidence: 96%
See 1 more Smart Citation
“…A very impressive hardness value was reached (after ECAP route Bc for four passes) of 110 HV, along with an ultimate compressive strength of 185 MPa. The hardness observed in the ECAP-compacted alloy was mainly attributed to the dispersion hardening of Y 2 O 3 particles [7].…”
Section: Contributionsmentioning
confidence: 96%
“…The ECAP process is a useful process for metallurgical studies of light alloys and especially for Mg, as shown by Ou et al [7], with the paper dealing with the Mg97Zn1Y2 alloy powders reinforced by Y 2 O 3 particles prepared by simultaneous synthesising of Y 2 O 3 particles and compacting of mechanically alloyed powders using equal channel angular pressing. They found that, after mechanical alloying for 20 h, the material consisted of α-Mg, Y and Y2O3 phases.…”
Section: Contributionsmentioning
confidence: 99%
“…Recently, many studies have been performed on the machinability of titanium alloy. [19][20][21][22][23] These studies on different grades of titanium alloy especially grade 5 (Ti-6Al-4V), which offers high strength, high corrosion resistance, and good performance at high temperature are summarized as below:…”
Section: Introductionmentioning
confidence: 99%
“…It can be easily machined by the electrical discharge machining (EDM) and electrochemical machining (ECM) processes [2]. Since the ECM process may affect the top layer of the machined surface, EDM is normally utilized for machining such alloy [3]. It is a novel type of machining in which material is removed by applying regulated electrical pulses between the tool electrode and the workpiece specimen, as illustrated in Figure 1 [4,5].…”
Section: Introductionmentioning
confidence: 99%